2000
DOI: 10.1097/00007890-200012270-00009
|View full text |Cite
|
Sign up to set email alerts
|

Continent Urinary Diversion in Preparation for Renal Transplantation

Abstract: This is one of the largest single series reported to date of renal transplantation into continent urinary diversions, and we commend the approach in carefully selected patients, but the difficulties must not be underestimated and the specific problems of intestinal urinary reservoirs have to be reckoned with. These procedures should be confined to centers with considerable experience with this type of surgery and its complications. Lifelong close surveillance is critical for the success of this concept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…In our series, as in the majority of published series, most patients suffered from spina bifida . Constructing a continent reservoir allowed a population that already faces a disability to avoid the inconveniences of a non‐continent diversion, at a time when the desire to preserve body image played an increasing role in patient care.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…In our series, as in the majority of published series, most patients suffered from spina bifida . Constructing a continent reservoir allowed a population that already faces a disability to avoid the inconveniences of a non‐continent diversion, at a time when the desire to preserve body image played an increasing role in patient care.…”
Section: Discussionmentioning
confidence: 60%
“…Nevertheless, despite tried‐and‐true techniques and satisfactory functional results, few patients suffering from end‐stage renal disease have benefited from this type of diversion. In all, we found reports of 48 transplantations in adults with a continent pouch since 1989, with just four authors reporting more than two patients (Table ) …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…They concluded that the use of intestinal conduits for transplantation should be minimized because of the high incidence of septic complications (57). In recent reports, the incidence of complications ranged from 47% to 62.5% (58–60). A high incidence of UTI is well documented with supravesical diversion, and represents the most common complication.…”
Section: Strategies To Treat Patients With An Abnormal Lower Urinary mentioning
confidence: 99%
“…Vor dem Hintergrund der guten Marburger/Würzburger Erfahrungen mit der Nierentransplantation in prätransplantationem angelegte Ileocoecalreservoirs bei insgesamt 12 Patienten mit aus verschiedensten Gründen geschädigten Harnblasen [29] erscheint es mir zumindest bei den oft wandverdickten, fibrosierten Harnblasen nach Urethralklappen risikoärmer zu sein, vor der Transplantation eine Blasenaugmentation oder ein kontinentes Reservoir mit Nabelstoma anzulegen. Da dem Schutz der Transplantatniere oberste Priorität gilt, ist in der Vorbereitung ein weitsichtiges Management sinnvoll.…”
Section: Schlussfolgerungunclassified